Pengaruh Media Linimasa Card Game (LCG) Terhadap Kesadaran Sejarah dan Hasil Belajar Peserta Didik Pada Mata Pelajaran Sejarah Kelas XI Di SMA Negeri 1 Lawang - Febriyanti, Hani Auliyah; Wahyu Djoko Sulistyo (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2025)
This study was motivated by the low historical awareness of students at SMA Negeri 1 Lawang despite their high academic performance in history. This is due to the use of monotonous and uninteractive learning media. The purpose of this study is to determine the effect of the Linimasa Card Game (LCG) media on students' historical awareness and academic performance in grade XI. The method used is quantitative with a quasi-experimental design of the non-equivalent control group type. The sample consists of 34 students in the control group and 35 students in the experimental group. Data analysis techniques included validity, reliability, normality, independent t-test, MANOVA, and simple linear regression tests. The results showed that the Linimasa Card Game (LCG) media significantly influenced historical awareness (Sig. 0.001 < 0.05) and learning outcomes (Sig. 0.008 < 0.05). The MANOVA test showed a Sig. value of 0.001 (p < 0.05), indicating the simultaneous effect of the media on both variables. The regression test showed that historical awareness contributed 46.9% to learning outcomes. The posttest average of the experimental class was higher than that of the control class, both in terms of historical awareness and learning outcomes. Thus, it can be concluded that the use of the Linimasa Card Game (LCG) is effective in improving students' historical awareness and learning outcomes.